The DiscoverFramework freeware toolkit for multivariate spatio-temporal environmental data visualization and evaluation. (September 2021) - Porter, Misty E.; Hill, Mary C.; Harris, Ted; Brookfield, Andrea; Li, Xingong
Abstract: The freeware DiscoverFramework provides new tools to build spatial and temporal data visualization applications accessible to stakeholders, policy makers, scientists, and educators. By focusing on environmental data and supporting applications accessible via laptops, tablets, and cell phones, the DiscoverFramework can be used to increase public awareness and inspire responsible use of complex environmental systems upon which human society depends. DiscoverFramework enables computer-savvy domain scientists to develop interactive applications using "Elements" and workflows defined to make visualization easy and address common problems such as spatio-temporal scales and user engagement. Two applications are used to demonstrate DiscoverFramework: DiscoverWater and DiscoverHABs. DiscoverWater uses Map, Chart, and Text Elements to relate streamflow changes to groundwater withdrawals. DiscoverHABs uses the Scenario Element to aid stakeholders, such as resource managers and users, struggling to identify when and where harmful algal blooms (HABs) are likely given that causal relations in these systems remain poorly understood. Highlights: Visualize complex spatio-temporal multivariate data sets with modular "Elements". Construct many environmental data applications using DiscoverFramework. Experience using DiscoverWater and DiscoverHABs applications. Explore important insights quickly using holistic data visualization.